An Analysis Of Legal Studies In Uncovering Crime Cases - Muhammad Fajrin Pane (INFOKUM, 2022)
Crown witnesses are seen as having the potential power in uncovering crimes. Moreover, crimes involve several actors who have developed strong bonds with each other and are closed, either through personal connections or business connections or through professional associations, such as corruption crimes. One of the efforts to tackle crime is through criminal law. Prevention of crime with criminal law is essentially also part of law enforcement efforts (especially criminal law enforcement). Even though criminal law enforcement in the context of crime prevention is not the only hope, its success is highly expected because it is in the field of law enforcement that the meaning of "a state based on law" is at stake. the importance of witnesses who are also perpetrators of crimes who are "inner-cycle criminals" because they are considered to have the potential to uncover crimes. Sometimes these "insiders" are the perpetrators involved in the crime. Apart from providing clues to investigators, these insiders occasionally participate in investigations. Finally, these insiders can become very important witnesses during trials, providing evidence in the first person, eyewitnesses of criminal activity.